A novel conserved family of Macro-like domains—putative new players in ADP-ribosylation signaling - Dudkiewicz, Małgorzata (PeerJ, 2019)
The presence of many completely uncharacterized proteins, even in well-studied organisms such as humans, seriously hampers a full understanding of the functioning of living cells. One such example is the human protein C12ORF4, which belongs to the DUF2362 family, present in many eukaryotic lineages and conserved in metazoans. The only functional information available on C12ORF4 (Chromosome 12 Open Reading Frame 4) is its involvement in mast cell degranulation and its being a genetic cause of autosomal intellectual disability. Bioinformatics analysis of the DUF2362 family provides strong evidence that it is a novel member of the Macro clan/superfamily. Sequence similarity analysis versus other representatives of the Macro superfamily of ADP-ribose-binding proteins and mapping sequence conservation on predicted three-dimensional structure provides hypotheses regarding the molecular function for members of the DUF2362 family. For example, the available functional data suggest a possible role for C12ORF4 in ADP-ribosylation signaling in asthma and related inflammatory diseases. This novel family appears to be a likely novel ADP-ribosylation “reader” and “eraser,” a previously unnoticed putative new player in cell signaling by this emerging post-translational modification.